The effect of reduced ankle dorsiflexion on lower extremity mechanics during landing: A systematic review - Mason-Mackay, A. R.; Whatman, C.; Reid, D. (Journal of Science and Medicine in Sport, 2017)
Objectives: To examine the evidence for effect of restricted ankle dorsiflexion range of motion on lower-extremity landing mechanics. Design: Literature review. Methods: Systematic search of the literature. Articles critiqued by two reviewers. Results: Six studies were identified that investigated the effect of restricted DF ROM on landing mechanics. Overall, results suggest that landing mechanics are altered with restricted DF ROM, but studies disagree as to the particular mechanical variables affected. Conclusions: There is evidence that restricted dorsiflexion range of motion may alter lower-extremity landing mechanics in a manner, which predisposes athletes to injury. Interpretation of results was made difficult by the variation in landing tasks investigated and the lack studies investigating sport-specific landing tasks. The focus of studies on specific mechanical variables rather than mechanical patterns and the analysis of pooled data in the presence of different compensation strategies between participants also made interpretation difficult. These areas require further research.